Strelchenko D. V. Language means of the English-speaking advertising discourse - Strelchenko D. V. (Philological Treatises, 2020)
The article deals with various language fillings of advertizing texts which are directed on realization of the main function: to convince the addressee to buy the advertized goods or service. Among widely usage of advertizing media language on different levels we allocate : the rhymed form of a slogan, a lexeme of a positive estimation, expressive-emotional lexemes, stylistic receptions and different aspects of semasiology), occasional innovations and etc.